2021
DOI: 10.1186/s12879-021-05786-5
|View full text |Cite
|
Sign up to set email alerts
|

The different manifestations of COVID-19 in adults and children: a cohort study in an intensive care unit

Abstract: Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has collapsed health systems worldwide. In adults, the virus causes severe acute respiratory distress syndrome (ARDS), while in children the disease seems to be milder, although a severe multisystem inflammatory syndrome (MIS-C) has been described. The aim was to describe and compare the characteristics of the severe COVID-19 disease in adults and children. Methods This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 33 publications
0
35
0
4
Order By: Relevance
“…Several studies from different countries have been reported their epidemiological findings for COVID-19 in children. [ 11 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from different countries have been reported their epidemiological findings for COVID-19 in children. [ 11 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to adults, only an extremely small percentage of children infected by SARS-CoV-2 had severe respiratory symptoms and progression to ARDS [ 5 , 36 ]. There is paucity of data on the occurrence of PARDS in pediatric patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of COVID-19 were seven times lower in younger children [ 26 ]. In general, adults were more prone to severe ARDS (acute respiratory distress syndrome), whereas children normally had milder symptoms, although some had multisymptom inflammatory syndrome (MIS-C) [ 60 ]. As with adults, not all children with COVID-19 have the same manifestations.…”
Section: Probable Explanations For Why Sars-cov-2 Positive Individuals Remain Asymptomatic or Have Mild Symptomsmentioning
confidence: 99%
“…Thus, some children may have more or less entry points for the virus than other children, and this may be associated with why some develop the disease. Whether or not children with COVID-19 were obese or had other health issues was not noted [ 60 ].…”
Section: Probable Explanations For Why Sars-cov-2 Positive Individuals Remain Asymptomatic or Have Mild Symptomsmentioning
confidence: 99%